Kinetic Studies on the Effect of Mn(II) on the Oxidation of α-Hydroxy Carboxylic Acids by Cr(VI) - Bikaneria, S.L.; Hiran, B.L. (Asian Journal of Chemistry, 2010)
Mn(II) catalysis in the chromic acid oxidation of lactic acid (LA), malic acid (MA), tartaric acid (TA) and citric acid (CA) in 50% acetic acid·50% water medium has been studied. Mn(II) retards' oxidation at low [Mn(II)]/[Cr(VI)] ratio but in H2SO4 (= 1.0 M) at high [Mn(II)]/[Cr(VI)] ratio 200 for lactic acid, 200 for malic acid and 500 for tartaric acid, rate of oxidation increases while for citric acid it is very low ratio (= 10). Rate under the positive catalysis is linearly proportional to [Mn(II)], [H2SO4] at ≥ 1.0 M, HCrO4- and obey Michaelis-Menten kinetics. Addition of sodium pyrophosphate decreases rate of oxidation. Energy of activation for uncatalysed, Cr(VI)-Mn(II) and catalysed reactions have been given.